2011
DOI: 10.1017/s0272263110000756
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Implicit and Explicit Linguistic Knowledge

Abstract: Although claims about explicit and implicit language knowledge are central to many debates in SLA, little research has been dedicated to measuring the two knowledge types (R. Ellis, 2004, 2005). The purpose of this study was to validate the use of the battery of tests reported in Ellis (2005) to measure implicit and explicit language knowledge. Whereas Ellis (2005) tested only second-language (L2) learners (of English), this study tested both L2 and heritage language (HL) learners (of Spanish). Results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
134
4
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 213 publications
(158 citation statements)
references
References 34 publications
16
134
4
4
Order By: Relevance
“…The authors stated that "accuracy scores of the written tasks could be taken to reflect ability with metalinguistic, explicit knowledge (typically acquired later)" (p. 514). These findings seem to corroborate those reported earlier (Bowles, 2011;Montrul, 2010;Potowski, 2014). Along these same lines, Montrul (2011), examined whether morphological variability differed significantly when comparing L2 and HL adult learners.…”
Section: L2 Vs Hl Writingsupporting
confidence: 93%
See 4 more Smart Citations
“…The authors stated that "accuracy scores of the written tasks could be taken to reflect ability with metalinguistic, explicit knowledge (typically acquired later)" (p. 514). These findings seem to corroborate those reported earlier (Bowles, 2011;Montrul, 2010;Potowski, 2014). Along these same lines, Montrul (2011), examined whether morphological variability differed significantly when comparing L2 and HL adult learners.…”
Section: L2 Vs Hl Writingsupporting
confidence: 93%
“…In this study, HL learners who were at a comparable curricular stage as L2 learners, benefited from a less controlled type of task. However, as previous studies have shown (e.g., Bowles, 2011), in more controlled type of writing tasks, HL learners appear to be outperformed by their L2 peers.…”
Section: Pedagogical Implicationsmentioning
confidence: 44%
See 3 more Smart Citations